2019
DOI: 10.3390/en12234439
|View full text |Cite
|
Sign up to set email alerts
|

Applying Artificial Neural Networks to Forecast European Union Allowance Prices: The Effect of Information from Pollutant-Related Sectors

Abstract: In this paper, we forecast the price of CO2 emission allowances using an artificial intelligence tool: neural networks. We were able to provide confident predictions of several future prices by processing a set of past data. Different model structures were tested. The influence of subjective economic and political decisions on price evolution leads to complex behavior that is hard to forecast. We analyzed correlations with different economic variables related to the price of CO2 emission allowances and found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This result contradicts the findings of Feng et al (2011), who used data from the first phase of the market, suggesting that, once allowances began to be allocated by auctioning, market operation changed. In contrast to Jaramillo and García (2019), the model proposed in this paper provides short-term forecasting prices, that is, it considers the allowances as financial assets, whose time evolution is not affected by the inclusion of additional variables apart from allowance price. Price evolution is compatible with an optimal temporal distribution of allowances.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result contradicts the findings of Feng et al (2011), who used data from the first phase of the market, suggesting that, once allowances began to be allocated by auctioning, market operation changed. In contrast to Jaramillo and García (2019), the model proposed in this paper provides short-term forecasting prices, that is, it considers the allowances as financial assets, whose time evolution is not affected by the inclusion of additional variables apart from allowance price. Price evolution is compatible with an optimal temporal distribution of allowances.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several authors have pointed out the possible influence of energy and fuel prices on the evolution of CO2 allowance prices (Paolella and Taschini, 2008;Alberola et al, 2009;Keppler and Mansanet-Bataller, 2010;Hammoudeh et al, 2014;Hammoudeh et al, 2015;Convery and Redmond, 2007;Boersen and Scholtens, 2014). In Jaramillo and García (2019), the influence of energy and raw material prices on this variable was studied by analyzing their correlation. It was found that only electricity and iron and steel prices were correlated with the price of CO2 allowances.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way two series are obtained: one describing the global trend of data and the other their seasonal and cyclic oscillations. It has provided good results when applied to electric consumption forecasting [20] and also to EUA prices prediction [33]. Another approximation to this decomposition is a regression algorithm that samples a dataset at different frequencies (MIDAS), which have been developed to deal with econometric series, and have been also applied to carbon prices forecasting [25].…”
Section: Introductionmentioning
confidence: 99%